PRINSIP-PRINSIP PENDIDIKAN NILAI - Abdul Wahab Syakhrani; Marlina Ulfah; Nadia Ramadina; Najma Sa’adah; Noor Azizah; Norliana (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
Value education aims to develop learners who are able to understand and apply values in their daily lives. It encompasses ethical aspects related to good and bad, as well as aesthetic aspects related to beauty, and plays a significant role in shaping positive character and behavior. The principles of value education serve as guidelines to ensure that the process of instilling values is systematic, planned, and effective, emphasizing not only knowledge but also internalization and practical application. Value education is implemented through four main principles: role modeling, learning, reinforcement, and assessment. These interconnected principles work together to form well-rounded character, enabling learners to consistently demonstrate positive behavior in everyday life.